Journal of Southeast Asian studies
The Journal of Southeast Asian Studies is one of the principal outlets for scholarly articles on Southeast Asia (Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, East Timor, Singapore, Thailand and Vietnam). Embracing a wide range of academic disciplines in the humanities and social sciences, the journal publishes manuscripts oriented toward a scholarly readership but written to be accessible to non-specialists. The extensive book review section includes works in Southeast Asian languages.